KOMBINASI TERAPI WARNA HIJAU, AROMATERAPI LAVENDER, DAN MUSIK UNTUK MENURUNKAN NYERI DAN KECEMASAN PERSALINAN - Ari Andriyani; Mahindria Vici Virahaju (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: The ideal application of holistic midwifery care is by paying attention to the psycho-neuro- endocrino-immuno aspect.Midwives are expected to be able to facilitate mothers to get a natural, safe, comfortable, calm and pain free maternity experience. Combination of green color, lavender aromatherapy and music have not been utilized as many as other non-pharmacological therapies to reduce maternal pain and anxiety. Objective: To determine the effectiveness of the combination of green color, lavender aromatherapy and music to reduce maternal pain and anxiety. Methods: A quasy-experimental study with pre-test and post-test control group design was applied. Sixty mothers giving birth were divided intocontrol and experimental group., The combination of green color therapy, lavender aromatherapy and therapeutic music were delivered to experimental group whilst control group got normal standard care. Pain and anxiety were measured before and after treatment and then analized by using statistical methods. Results: there was a significant difference between the level of pain in the treatment group and the control group (p = 0,0009) but there was no significant difference in the level of anxiety (p = 0,313). Conclusion:The combination of therapiesare more effective in reducing pain in maternity as compared to conventional method. Keywords: Green Color Therapy, labor pain, lavender aromatherapy, maternal anxiety, music therapy.